Chlamydia-like organisms in ctenidia and mantle cells of the Japanese oyster Crassostrea ggias from the French Atlantic coast - Renault, Tristan; Cochennec, Nathalie (Inter-Research, 1995)
Grossly visible lesions of the ctenidia and occasional mortalities in Japanese oyster Crassostrea gigas from the Atlantic French coast were reported in 1992-1993. From August 1992 to March 1993, 235 living oysters were collected to determine the cause of tissue lesions and mortalities. Microscopical examination of fixed, stained sections revealed that 53 2% of these oysters had ctenidia and mantle lesions associated with irregular basophllic and Feulgen positive cytoplasmic inclusion bodies. Ultrastructurally, the infectious agent was a chlamydia-like organism. Indirect fluorescent and peroxidase conjugated antibody tests suggested that this agent might share common antigens with the prokaryotic agent Chlamydia psittaci, strain ovis